Pemanfaatan Materi Kearifan Lokal dalam Pembelajaran IPS Kelas 6 untuk Meningkatkan Keterampilan Komunikasi Siswa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of integrating local wisdom materials in Social Studies (IPS) to improve the communication skills of 6th-grade elementary school students. Local wisdom is seen as a contextual and relevant learning instrument for students' cultural identity. The research method used is a literature study (library research) by analyzing the results of research on the development of learning tools based on local culture. The study results show that the use of materials based on local wisdom significantly encourages more active social interaction in the classroom, increases students' courage in expressing opinions, and strengthens democratic values in communication. The conclusion of this study confirms that local wisdom functions as a bridge between social theory and real communication practices, which ultimately improves students' interpersonal competence at the elementary school level.